2012
DOI: 10.1111/1440-1630.12004
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of older adults' occupational adaptation following a stroke

Abstract: These findings support an empowering approach to therapy, facilitating clients to identify and utilise individually appropriate coping strategies to negotiate negative emotions and apprehension and enable the required personal qualities for occupational adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
3
31
0
2
Order By: Relevance
“…Acknowledgement of positive feelings can be a powerful impetus for discovering what is meaningful, pleasant, and possible, and these experiences and activities can be incorporated into a productive recovery and life journey. 41 Personal strengths can be employed to negotiate limitations, 42 and improved confidence and self-efficacy can promote quality of life post-stroke. 43,44 …”
Section: Discussionmentioning
confidence: 99%
“…Acknowledgement of positive feelings can be a powerful impetus for discovering what is meaningful, pleasant, and possible, and these experiences and activities can be incorporated into a productive recovery and life journey. 41 Personal strengths can be employed to negotiate limitations, 42 and improved confidence and self-efficacy can promote quality of life post-stroke. 43,44 …”
Section: Discussionmentioning
confidence: 99%
“…They consulted with trusted others about their thoughts, which helped them feel recognized and supported. Previous research has shown that sympathetic supporters are strong sources of encouragement for coping with difficult feelings (Sjölander & Berterö, 2008;West, Stewart, Foster, & Usher, 2012;Williams & Murray, 2013).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…This is relevant because although everyday life is conceptually often equated with the antithesis of importance, it is what occupies essentially all our time. It is within the contexts of everyday life where a person's life-worlds after stroke are altered (5), chaos or a breakdown in habit patterns redefine the formerly taken-for-granted (6), and where fear and apprehension can arise (7). Being able to negotiate new challenges and finding ways to influence daily situations through the doing of everyday life is perhaps one of the most important tenets in considering how people make things happen by their own actions.…”
Section: Introductionmentioning
confidence: 99%